Biological evaluation of semi-synthetic isoindolinone isomers produced by Stachybotrys chartarum - Fischle, Alica; Schreiber, Ulrich; Haupt, Viola; Schimang, Felix; Schürmann, Lina; Behrens, Matthias; Hübner, Florian; Esselen, Melanie; Kalinin, Dmitrii V.; Kalinina, Svetlana A. (Frontiers in Fungal Biology, 2024)
The filamentous fungus Stachybotrys chartarum is rich in meroterpenoid secondary metabolites, some of which carry o-dialdehyde moieties, which are readily derivatized to isoindolinones by addition of primary amines. The structural diversity of phenylspirodrimanes, in particular, is linked to a wide range of biological activities, making them ideal candidates for semi-synthetic modification. In this study, acetoxystachybotrydial acetate was reacted with l-tryptophan and tryptamine, resulting in the detection of both regiospecific isomeric structures - a rare and significant finding that enabled the examination of four novel reaction products. Besides their successful purification, a detailed report on their isomer-specific behavior with regard to chromatographic retention, UV-spectral specificities, nuclear magnetic resonances, and mass spectrometric fragmentation is given. Furthermore, a comprehensive insight into each compounds’ unique effect within the tested biological assays is provided, which include cytotoxicity, genotoxicity, their biological activity against serine proteases of the blood coagulation cascade, and in vitro hepatic metabolism, always in comparison to the non-derivatized substance. Ultimately, each isomer can be distinguished already during the purification process, which extends to the biological assays where we present one less cytotoxic, faster metabolized, and more active regio-isomeric phenylspirodrimane-derivative.